1992
DOI: 10.1007/bf00042429
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the elastic T-stress in surface-cracked plates using the line-spring method

Abstract: The elastic T-stress has been found to be an important parameter in characterizing the very near tip elastic-plastic stress state under 2-D plane strain conditions (Larsson and Carlsson [1]; Bilby et al. [2]; Beteg6n and Hancock [3]; etc.). Several computational methods have been developed to evaluate the T-stress (Larsson and Carlsson [1]; Kfouri [4]; Sham [5]). However, none of these methods can be readily adapted to calculate the elastic T-stress in a surface-cracked plate (SCP), which is essentially 3-D in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Generally, very fine meshes are required to accurately determine the T-stress when using this method. The domain over which the stresses are calculated is arbitrary but it should not be too far away from the crack tip as higher order terms become more significant [9].…”
Section: Numerical Evaluation Of the T-stressmentioning
confidence: 99%
“…Generally, very fine meshes are required to accurately determine the T-stress when using this method. The domain over which the stresses are calculated is arbitrary but it should not be too far away from the crack tip as higher order terms become more significant [9].…”
Section: Numerical Evaluation Of the T-stressmentioning
confidence: 99%
“…2/ao, Z/H >> 1, the problems can be studied using the 'line spring' concept originally developed by Rice and Levy [37] for treating part-through cracks in elastic plates. The line-spring method has already been applied to calculate the T-stress for surfacecracked plate by Wang and Parks [17]. On the other hand, for short wavelength perturbations, i.e.…”
Section: K Smt ) (44)mentioning
confidence: 99%
“…The fact that T significantly affects the stress triaxiality in the very near-tip elastic-plastic fields has motivated the development of a two-parameter characterization methodology [9][10][11][12][13][14][15][16][17]. Such two-parameter characterization using J and T for the elasti~plastic crack-tip fields has been shown, in the literature quoted above, to provide exceptional improvement in describing local crack-tip stress triaxiality on the scale of fracture process zone size, as compared to any single-parameter crack-tip description, for a variety of crack configurations and loadings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement of elastic-plastic FE analyses together with many variables to be considered may hamper the use of the J-Q-M theory in practical application. This aspect has been discussed in detail in a recent paper of Thaulow et al (2004), and they suggested that constraint and mismatch corrections can be made available in practice by line-spring calculations (Wang and Parks 1992;Lee and Parks 1995;Jayadevan et al 2005). As the effects of mismatch in yield strength have been extensively investigated, it would be useful to characterize interfacial crack tip stress fields for another limiting case of bi-materials having the mismatch in plastic strain hardening with the same yield strength.…”
Section: Introductionmentioning
confidence: 97%